2016
DOI: 10.1186/s13075-016-1173-0
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence, sensitivity and specificity of antibodies against carbamylated proteins in a monocentric cohort of patients with rheumatoid arthritis and other autoimmune rheumatic diseases

Abstract: BackgroundAntibodies against carbamylated proteins (anti-CarP) have been recently identified in the sera of patients with rheumatoid arthritis (RA). The objective of the study was to evaluate the prevalence, sensitivity and specificity of anti-CarP compared to anti-citrullinated peptide antibodies (ACPA) and rheumatoid factor (RF), replicating the existing data in a large cohort of Italian patients with RA and extending the evaluation to other autoimmune rheumatic diseases (AIRDs).MethodsSerum samples (n = 607… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
(43 reference statements)
7
31
1
Order By: Relevance
“…Our results demonstrated a significant correlation between autophagy and carbamylation levels in mononuclear cells of naïve RA patients, although, at present, analysis of the relationship between clinical and laboratory parameters, and monocyte levels of autophagy and/or carbamylation, did not reveal any statistically significant correlation. It could be considered an early trigger for the appearance of anti-CarP Ab [39,40], which in turn precede the onset of RA [34]. Indeed, in this study we observed the presence of anti-CarP antibodies only in 23.3% of early-active RA patients, supporting the view that carbamylation represents an early trigger, which precedes the appearance of the antibodies.…”
Section: Discussionsupporting
confidence: 81%
“…Our results demonstrated a significant correlation between autophagy and carbamylation levels in mononuclear cells of naïve RA patients, although, at present, analysis of the relationship between clinical and laboratory parameters, and monocyte levels of autophagy and/or carbamylation, did not reveal any statistically significant correlation. It could be considered an early trigger for the appearance of anti-CarP Ab [39,40], which in turn precede the onset of RA [34]. Indeed, in this study we observed the presence of anti-CarP antibodies only in 23.3% of early-active RA patients, supporting the view that carbamylation represents an early trigger, which precedes the appearance of the antibodies.…”
Section: Discussionsupporting
confidence: 81%
“…We observed that a combination such as (1) the presence of PD grade ≥2 articular synovitis or (2) the presence of PD grade ≥ 1 articular synovitis and RF and/or ACPA positivity, or the combination of (1) the presence of cPD grade 3 or (2) cPD grade ≥2 and RF and/or ACPA positivity had the best‐balanced diagnostic performance (Table ). The performance of ACPA for diagnosing RA is more specific than that of RF, but our present findings suggest the utility of the use of RF and/or ACPA for the early diagnosis of RA, probably due to the combinational use of the PD signal provided by US.…”
Section: Discussionsupporting
confidence: 60%
“…In brief, as we described previously [22], Nunc Maxisorp plates (Thermo Scientific) were coated overnight at + 4 °C with non-modified FCS and Ca-FCS (10 μg/ml in carbonate bicarbonate buffer). After washing plates were blocked with phosphate buffered saline (PBS) 1% bovine serum albumin (BSA) (Sigma) for 6 h at + 4 °C.…”
Section: Methodsmentioning
confidence: 99%